1999
DOI: 10.1023/a:1007653709188
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The prevalence of asthma and respiratory symptoms in south-central Durban, one of the most heavily polluted areas of South Africa, has been determined using a cross-sectional survey of 213 households in the communities of Merewent (97% Indians) and Austerville (98% coloreds). The study population consisted of 367 children (less than 17 years old) and 693 adults. About 10% of the children and 12% of adults reported doctor diagnosed asthma. The self-reported prevalence rates for wheezing (3740%) and attacks of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 22 publications
3
16
0
1
Order By: Relevance
“…Chronic bronchitis and shortness of breath prevalence in Kejetia is similar to some other studies among rural Canadian swine farmers (Dosman et al, 1988) and urban South African adults (Nriagu et al, 1999). Usual phlegm production, usual phlegm production for longer than three months, and wheezing are higher in Kejetia than found in other groups of rural and urban adults (Dosman et al, 1988; Gallotti et al, 2006; Nriagu et al, 1999).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Chronic bronchitis and shortness of breath prevalence in Kejetia is similar to some other studies among rural Canadian swine farmers (Dosman et al, 1988) and urban South African adults (Nriagu et al, 1999). Usual phlegm production, usual phlegm production for longer than three months, and wheezing are higher in Kejetia than found in other groups of rural and urban adults (Dosman et al, 1988; Gallotti et al, 2006; Nriagu et al, 1999).…”
Section: Discussionsupporting
confidence: 89%
“…Chronic bronchitis and shortness of breath prevalence in Kejetia is similar to some other studies among rural Canadian swine farmers (Dosman et al, 1988) and urban South African adults (Nriagu et al, 1999). Usual phlegm production, usual phlegm production for longer than three months, and wheezing are higher in Kejetia than found in other groups of rural and urban adults (Dosman et al, 1988; Gallotti et al, 2006; Nriagu et al, 1999). In Gorogo, cough for longer than three months, usual phlegm production, usual phlegm production for longer than three months, chronic bronchitis, breathlessness when walking, wheezing, and shortness of breath are all generally lower than other potentially exposed and non-exposed groups (Gamsky et al, 1992; Gallotti et al, 2006; Nriagu et al, 1999; Dosman et al, 1988).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…[14] In south Durban children aged under 17 years, parents reported that 16.3% had experienced attacks of shortness of breath with wheeze during the last 12 months, and that 10% had ever been diagnosed with asthma. [15] The ISAAC-based prevalences show wide variation between countries in Africa, prevalences of wheeze symptoms ranging from 4.0% to 21.5%. [7] Our rates of 14.8% for doctor-diagnosed asthma and 24.5% for ever wheezing reported by the caregivers are within the range of other South African and international studies.…”
Section: Discussionmentioning
confidence: 99%